Reasons for the use of masks in open areas after the Peruvian government announced that it will no longer be mandatory in the context of COVID-19 in 2022 - Caycho-Rodríguez, Tomás (2023)
Introduction: In Peru, a high proportion of fully immunized people against COVID-19 has been achieved, which has mitigated the severity of the disease. Thus, under the recommendation of experts, the Peruvian government issued Supreme Decree 118-2022-PCM, which indicated that the use of masks is optional in open and ventilated enclosed spaces as of October 1, 2022. Objective: The aim of the present study was to find out the reasons why people continued to wear masks even though it was not mandatory in outdoor environments. Methods: A total of 335 people participated, with an average age of 26.11 years (73.1% women). A data collection form was prepared where sociodemographic and health information was requested; in addition, the question "Why do you continue to wear mask despite it being optional in open and closed ventilated spaces?" was included. The data obtained from the last open question of the instrument was analyzed by means of a discursive textual analysis (DTA) and an exploratory analysis through IRAMUTEQ. Results: Results indicate that people continue to wear masks, despite the lifting of the restrictions, to avoid contagion of COVID-19 and other respiratory diseases. In addition, the prevention of possible infection and transmission of the virus also focused on the family and vulnerable people. Discussion: It is concluded that the practice of wearing masks may be influenced by individual perceptions of risk and interpretations of responsibility and solidarity towards others.